Gambling on Culture in Canada: Gaming as a Source of Funding for Culture, the Arts and Heritage - Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 2002)
This study set out to examine the extent to which cultural activity in Canada is being funded through gaming revenues. It uncovered a tangled web of gaming activities and an even more tangled web of revenue allocations from those activities. Gambling in Canada has been legal since 1969 when an amendment to the Criminal Code gave the provinces authority to operate lottery schemes and casinos and to license charitable and religious organizations to conduct lottery schemes. In 1979, a federal-provincial agreement was entered into whereby the federal government agreed to abstain from conducting and managing lottery schemes. In return, the provinces agreed to pay the federal government the equivalent of C$24 million (in 1979 dollars) annually.
Keywords: Culture; Arts; Heritage; Gambling